Multilayer composite positive electrode of lithium-sodium dual ion system, hybrid capacitor and preparation method of hybrid capacitor
By adopting a multi-layer composite positive electrode structure with a lithium-sodium dual-ion system in the lithium-ion hybrid capacitor, the poor performance of the lithium-ion hybrid capacitor in the low-temperature environment is solved, and higher low-temperature charging and discharge performance and rate performance are achieved.
Patent Information
- Application Number
- CN202410529468.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-29
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-04-29
AI Technical Summary
Existing lithium-ion hybrid capacitors show poor charging and discharging performance in low temperature environments and cannot work effectively below -40°C.
A multi-layer composite positive electrode structure with a lithium-sodium dual-ion system is adopted. The inner and outer layers contain lithium storage materials and sodium storage materials respectively, and are mixed with capacitive carbon to improve the low-temperature performance of the capacitor.
While keeping the energy density unchanged, the low-temperature charge and discharge performance and rate performance of the hybrid capacitor are significantly improved.
Smart Images

Figure CN118431437B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of capacitors, and in particular to a multilayer composite positive electrode of a lithium-sodium dual ion system, a hybrid capacitor and a preparation method of the hybrid capacitor. Background Art
[0002] Supercapacitors and lithium / sodium-ion batteries are the two most popular energy storage devices on the market. Supercapacitors include double-layer capacitors based on the double-layer energy storage principle, pseudocapacitors based on the redox pseudocapacitor principle, and hybrid capacitors that combine double-layer capacitors and lithium / sodium-ion batteries. They have the advantages of high power density, short charge and discharge time, and long cycle life, but also have disadvantages such as relatively low energy density. Lithium-ion batteries are green secondary batteries with high energy density, high average output voltage, low self-discharge, and no toxic substances. The energy density can reach up to 250Wh / kg and the maximum operating voltage can reach 4.5V. Sodium-ion batteries are batteries developed in the lithium-ion battery system. Their rate and low-temperature performance are significantly improved compared to lithium-ion batteries, but their energy density has decreased.
[0003] The electrical performance of commercial lithium-ion hybrid capacitors is between that of double-layer capacitors and lithium-ion batteries. The power density is improved by introducing a certain proportion of capacitor carbon into the positive and negative electrodes of lithium-ion batteries. For example, patent CN105161309B discloses a lithium-ion hybrid capacitor, whose battery cell is obtained by winding or laminating a positive electrode sheet, a negative electrode sheet, and a diaphragm placed between the positive and negative electrodes. However, due to the electrolyte system, the low-temperature performance is almost equivalent to that of lithium-ion batteries, and it is impossible to achieve -40°C application and rate charging. Therefore, an ideal solution is needed. Summary of the invention
[0004] In order to overcome the problem of poor low-temperature performance of lithium-ion hybrid capacitors, the present invention provides a multilayer composite positive electrode of a lithium-sodium dual ion system, a hybrid capacitor and a preparation method of a hybrid capacitor. The design and composite are carried out from the structure of the positive electrode pole piece. The pole piece includes an inner and outer layer structure, one layer includes a lithium storage material, and the other layer includes a sodium storage material. The sodium ion system improves the low-temperature performance of the capacitor, and the lithium ion system ensures the energy density, thereby improving the low-temperature performance of the device without reducing the energy density of the hybrid capacitor. Both layers of electrodes are mixed with capacitor carbon, and have both electrochemical energy storage and physical adsorption energy storage modes.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The multilayer composite positive electrode of the lithium-sodium dual ion system has a current collector in the middle, inner layers coated on both sides of the current collector, and an outer layer coated on the outside of the inner layer. The inner layer adopts a lithium ion / capacitor carbon hybrid electrode, and the outer layer adopts a sodium ion / capacitor carbon hybrid electrode. The coating surface density ratio of the inner layer and the outer layer is 1:(0.25-4).
[0007] Preferably, the inner layer comprises 50-80% by mass of lithium metal oxide, wherein the lithium metal oxide is selected from LiFePO 4 、NCM / NCA ternary cathode、LiFeMnPO 4 One or more of .
[0008] Preferably, the inner layer contains 50-80% lithium metal oxide, 10-40% capacitor carbon, 4-10% binder and 4-10% conductive agent, the proportions are by mass, and the sum of the proportions of each component is 100%.
[0009] Preferably, the outer layer comprises 40-70% by mass of a sodium metal compound, and the sodium metal compound is selected from one or more of polyanion-type, oxide-type, and Prussian blue-type sodium metal compound materials.
[0010] Preferably, the outer layer contains 40-70% sodium metal compound, 20-50% capacitor carbon, 4-10% binder and 4-10% conductive agent, the proportions are by mass, and the sum of the proportions of each component is 100%.
[0011] Preferably, the capacitor carbon is selected from one or more of activated carbon, mesoporous carbon, and carbon aerogel; the binder is selected from one or more of SBR, CMC, PTFE, PVDF, and PAA; and the conductive agent is selected from one or more of conductive carbon black, Ketjen carbon, graphene, and carbon nanotubes.
[0012] The present invention also provides a hybrid capacitor of a lithium-sodium dual ion system, wherein the positive electrode of the hybrid capacitor is a multilayer composite positive electrode of the lithium-sodium dual ion system.
[0013] Preferably, the negative electrode contains 60-85% by mass of active material, 5-30% of capacitor carbon, 4-10% of binder, and 4-10% of conductive agent, and the sum of the proportions of each component is 100%; the active material is a mixture of soft carbon and hard carbon.
[0014] Preferably, the electrolyte comprises positive ions, negative ions and an ester solvent, wherein the positive ions are Li + and Na + Composition: negative ions are selected from BF 4 - , ClO 4 - PF 6 - 、FSI- One or more; the ester solvent is selected from one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, and propylene carbonate. Preferably, the ratio of lithium ions to sodium ions in the electrolyte is consistent with that of the positive electrode.
[0015] Preferably, the positive electrode current collector of the hybrid capacitor is made of carbon-coated aluminum foil or corroded aluminum foil, and the negative electrode current collector is made of carbon-coated copper foil or copper foil; the diaphragm of the hybrid capacitor is one of PP, PE, PET, cellulose, aramid, spandex, polyester, polyimide, polyamide, or a composite coating diaphragm with the above materials as the base film.
[0016] The present invention also provides a method for preparing the hybrid capacitor of the lithium-sodium dual ion system, comprising the following steps:
[0017] 1) Mix the inner positive electrode slurry and the outer positive electrode slurry in a corresponding ratio to form a slurry, and control the viscosity to be 2000-3000cps;
[0018] 2) coating the two slurries on the positive electrode current collector at the same time, controlling the coating surface density ratio of the two slurries, and rolling and cutting to obtain the positive electrode;
[0019] 3) pulping, coating, rolling and cutting the negative electrode components to obtain a negative electrode;
[0020] 4) Winding the positive electrode, negative electrode and separator and assembling them according to the monomer structure;
[0021] 5) Drying, liquid injection, aging and testing of the monomer.
[0022] Therefore, the beneficial effects of the present invention are as follows: compared with the existing lithium ion hybrid capacitor, the multilayer electrode structure hybrid capacitor of the lithium sodium dual ion system of the present invention further improves the low temperature charge and discharge performance of the hybrid capacitor while maintaining the energy density unchanged, and improves the rate performance of the hybrid capacitor. Because the Stokes radius of sodium ions is smaller than that of lithium ions, sodium ion electrolytes of the same concentration have higher conductivity; in addition, sodium ions have lower solvation energy, which makes sodium ions have faster kinetic properties in electrolytes, thereby giving sodium ion capacitors excellent rate performance and low temperature performance, but because the mass of sodium ions is larger than that of lithium ions, its energy density is lower than that of lithium ion hybrid capacitors. The double electric layer electrode structure of the lithium sodium dual ion system, the sodium ion system improves the low temperature performance, and the lithium ion system ensures the energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic structural diagram of a multilayer composite positive electrode of a lithium-sodium dual ion system of the present invention;
[0024] In the figure, 1, current collector, 2, inner layer, 3, outer layer. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is further described below through specific embodiments.
[0026] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art. Unless otherwise specified, parts are all weight parts, temperatures are expressed in ° C or at ambient temperature, and pressures are atmospheric pressure or near atmospheric pressure. There are many variations and combinations of reaction conditions (such as component concentrations, desired solvents, solvent mixtures, temperatures, pressures, and other reaction ranges) and conditions that can be used to optimize the purity and yield of the product obtained by the method, and only reasonable routine experiments will be required to optimize such method conditions.
[0027] Example
[0028] 1. Multilayer composite cathode of lithium-sodium dual ion system
[0029] A multilayer composite positive electrode of a lithium-sodium dual ion system, such as Figure 1 As shown, the current collector 1 is in the middle, the inner layer 2 is coated on both sides of the current collector 1, the outer layer 3 is coated on the outer side of the inner layer 2, and the coating surface density ratio of the inner layer 2 and the outer layer 3 is 1:(0.25-4).
[0030] The current collector of the positive electrode is made of carbon-coated aluminum foil or corroded aluminum foil.
[0031] The inner layer adopts a lithium ion / capacitor carbon mixed electrode. The inner layer contains 50-80% lithium metal oxide, 10-40% capacitor carbon, 4-10% binder and 4-10% conductive agent, the proportions are by mass, and the sum of the proportions of each component is 100%; the lithium metal oxide is selected from LiFePO 4 、NCM / NCA ternary cathode、LiFeMnPO 4 The capacitor carbon is selected from one or more of activated carbon, mesoporous carbon, and carbon aerogel; the binder is selected from one or more of SBR, CMC, PTFE, PVDF, and PAA; and the conductive agent is selected from one or more of conductive carbon black, Ketjen carbon, graphene, and carbon nanotubes.
[0032] The outer layer adopts a sodium ion / capacitor carbon mixed electrode. The outer layer contains 40-70% sodium metal compound, 20-50% capacitor carbon, 4-10% binder and 4-10% conductive agent, the proportion is the mass proportion, and the sum of the proportions of each component is 100%; the sodium metal compound is selected from one or more of polyanion type, oxide type, and Prussian blue type sodium metal compound materials. The capacitor carbon is selected from one or more of activated carbon, mesoporous carbon, and carbon aerogel, and the binder is selected from one or more of SBR, CMC, PTFE, PVDF, and PAA; the conductive agent is selected from one or more of conductive carbon black, Ketjen carbon, graphene, and carbon nanotubes.
[0033] 2. Hybrid capacitor containing the above-mentioned multilayer composite positive electrode of lithium sodium dual ion system
[0034] A hybrid capacitor of a lithium-sodium dual-ion system includes a positive electrode, a negative electrode and an electrolyte.
[0035] The positive electrode is a multilayer composite positive electrode of the lithium-sodium dual ion system.
[0036] The negative electrode contains 60-85% active material, 5-30% capacitor carbon, 4-10% binder, and 4-10% conductive agent by mass, and the sum of the proportions of each component is 100%; the active material is a mixture of soft carbon and hard carbon. The current collector of the negative electrode adopts carbon-coated copper foil or copper foil.
[0037] The electrolyte includes positive ions, negative ions and ester solvents. The positive ions are composed of lithium ions and sodium ions. The ratio of lithium ions to sodium ions in the electrolyte is preferably consistent with that of the positive electrode. The negative ions are selected from BF 4 - , ClO 4 - PF 6 - 、FSI - One or more; the ester solvent is selected from one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC), and the salt concentration in the electrolyte is 0.8-1.2 mol / L.
[0038] The diaphragm is one of PP, PE, PET, cellulose, aramid, spandex, polyester, polyimide, polyamide, or a composite coating diaphragm with the above materials as base film.
[0039] 3. Preparation method of the above hybrid capacitor
[0040] The present invention also provides a method for preparing the hybrid capacitor of the lithium-sodium dual ion system, comprising the following steps:
[0041] 1) The inner positive electrode slurry and the outer positive electrode slurry are mixed in corresponding proportions to form a slurry, and the viscosity is controlled at 2000-3000cps; if the viscosity is too low, the stability of the slurry is poor, the slurry is easy to settle and agglomerate, and it is easy to overflow during the coating process; if the viscosity is too high, scratches are easy to occur during the coating process, affecting the appearance and performance of the electrode.
[0042] 2) coating the two slurries on the positive electrode current collector at the same time, controlling the coating surface density ratio of the two slurries, and rolling and cutting to obtain the positive electrode;
[0043] 3) pulping, coating, rolling and cutting the negative electrode components to obtain a negative electrode;
[0044] 4) Winding the positive electrode, negative electrode and separator and assembling them according to the monomer structure;
[0045] 5) Dry, inject, age and test the monomer. It should be noted that the drying temperature needs to match the diaphragm, and the electrolyte injection volume needs to be adjusted according to the actual immersion liquid absorption.
[0046] Example 1
[0047] A hybrid capacitor of a lithium-sodium dual-ion system comprises a positive electrode, a negative electrode and an electrolyte.
[0048] (1) The formula of the positive electrode slurry of the inner positive electrode layer is lithium iron phosphate: activated carbon: SBR / CMC: SP with a mass ratio of 80:10:4:6. The formula of the positive electrode slurry of the outer positive electrode layer is sodium iron pyrophosphate: activated carbon: PVDF: SP with a mass ratio of 60:30:5:5. The positive electrode current collector is carbon-coated aluminum foil.
[0049] The inner positive electrode slurry and the outer positive electrode slurry are mixed in a corresponding ratio to form a slurry, and the viscosity is controlled at 2000-3000cps. The two slurries are coated on the carbon-coated aluminum foil at the same time, and the coating surface density ratio of the inner and outer slurries is controlled to be 3:4. The positive electrode coating thickness is 130μm on a single side (i.e., the thickness of the inner and outer layers on one side of the current collector) and the positive electrode is obtained after rolling and cutting.
[0050] (2) Negative electrode
[0051] The formula of negative electrode components is hard carbon: soft carbon: activated carbon: SBR / CMC: SP with a mass ratio of 40:40:10:5:5. The current collector of the negative electrode adopts carbon-coated copper foil.
[0052] The negative electrode components are pulped, coated, rolled and cut according to conventional methods to obtain a negative electrode.
[0053] (3) Assembly
[0054] The positive electrode, negative electrode and separator PP prepared above are wound and assembled according to a monomer structure.
[0055] The monomer is dried and injected, and the electrolyte uses DEC / EMC / PC solvent and Li + / Na + (1:1) positive ions and PF 6 - / FSI - The electrolyte is composed of (1:1) negative ions. The monomers are subjected to formation and electrical performance tests, as well as low temperature performance tests and 5C cycle life tests.
[0056] Example 2
[0057] The difference from Example 1 is that the ratio of the inner and outer coating surface density of the positive electrode, the formula of the negative electrode and the positive ion Li + / Na + Proportion.
[0058] A hybrid capacitor of a lithium-sodium dual-ion system comprises a positive electrode, a negative electrode and an electrolyte.
[0059] (1) The formula of the positive electrode slurry of the inner positive electrode layer is lithium iron phosphate: activated carbon: SBR / CMC: SP with a mass ratio of 80:10:4:6. The formula of the positive electrode slurry of the outer positive electrode layer is sodium iron pyrophosphate: activated carbon: PVDF: SP with a mass ratio of 60:30:5:5. The positive electrode current collector is carbon-coated aluminum foil.
[0060] The inner positive electrode slurry and the outer positive electrode slurry are mixed in a corresponding ratio to form a slurry, and the viscosity is controlled at 2000-3000cps. The two slurries are coated on the carbon-coated aluminum foil at the same time, and the coating surface density ratio of the inner and outer slurries is controlled to be 4:1. The positive electrode coating thickness is 130μm on a single side, and the positive electrode is obtained after rolling and slitting.
[0061] (2) Negative electrode
[0062] The formula of negative electrode components is hard carbon: soft carbon: activated carbon: SBR / CMC: SP with a mass ratio of 20:60:10:5:5. The current collector of the negative electrode is carbon-coated copper foil.
[0063] The negative electrode components are pulped, coated, rolled and cut according to conventional methods to obtain a negative electrode.
[0064] (3) Assembly
[0065] The positive electrode, negative electrode and separator PP prepared above are wound and assembled according to a monomer structure.
[0066] The monomer is dried and injected, and the electrolyte uses DEC / EMC / PC solvent and Li+ / Na + (4:1) positive ions and PF 6 - / FSI - The electrolyte is composed of (1:1) negative ions. The monomers are subjected to formation and electrical performance tests, as well as low temperature performance tests and 5C cycle life tests.
[0067] Example 3
[0068] The difference from Example 1 is that the ratio of the inner and outer coating surface density of the positive electrode, the formula of the negative electrode and the positive ion Li + / Na + Proportion.
[0069] A hybrid capacitor of a lithium-sodium dual-ion system comprises a positive electrode, a negative electrode and an electrolyte.
[0070] (1) The formula of the positive electrode slurry of the inner positive electrode layer is lithium iron phosphate: activated carbon: SBR / CMC: SP with a mass ratio of 80:10:4:6. The formula of the positive electrode slurry of the outer positive electrode layer is sodium iron pyrophosphate: activated carbon: PVDF: SP with a mass ratio of 60:30:5:5. The positive electrode current collector is carbon-coated aluminum foil.
[0071] The inner positive electrode slurry and the outer positive electrode slurry are mixed in a corresponding ratio to form a slurry, and the viscosity is controlled at 2000-3000cps. The two slurries are coated on the carbon-coated aluminum foil at the same time, and the coating surface density ratio of the inner and outer slurries is controlled to be 1:4. The positive electrode coating thickness is 130μm on a single side, and the positive electrode is obtained after rolling and slitting.
[0072] (2) Negative electrode
[0073] The formula of negative electrode components is hard carbon: soft carbon: activated carbon: SBR / CMC: SP with a mass ratio of 60:20:10:5:5. The current collector of the negative electrode adopts carbon-coated copper foil.
[0074] The negative electrode components are pulped, coated, rolled and cut according to conventional methods to obtain a negative electrode.
[0075] (3) Assembly
[0076] The positive electrode, negative electrode and separator PP prepared above are wound and assembled according to a monomer structure.
[0077] The monomer is dried and injected, and the electrolyte uses DEC / EMC / PC solvent and Li + / Na + (1:4) positive ions and PF 6 - / FSI -The electrolyte is composed of (1:1) negative ions. The monomers are subjected to formation and electrical performance tests, as well as low temperature performance tests and 5C cycle life tests.
[0078] Example 4
[0079] A hybrid capacitor of a lithium-sodium dual-ion system comprises a positive electrode, a negative electrode and an electrolyte.
[0080] (1) The formula of the positive electrode slurry in the inner layer of the positive electrode is NCM: activated carbon: PVDF: SP with a mass ratio of 80:10:4:6. The formula of the positive electrode slurry in the outer layer is layered oxide: activated carbon: PVDF: SP with a mass ratio of 60:30:5:5. The positive electrode current collector is carbon-coated aluminum foil.
[0081] The inner positive electrode slurry and the outer positive electrode slurry are mixed in a corresponding ratio to form a slurry, and the viscosity is controlled at 2000-3000cps. The two slurries are coated on the carbon-coated aluminum foil at the same time, and the coating surface density ratio of the inner and outer slurries is controlled to be 3:4. The positive electrode coating thickness is 130μm on a single side, and the positive electrode is obtained after rolling and slitting.
[0082] (2) Negative electrode
[0083] The formula of negative electrode components is hard carbon: soft carbon: activated carbon: SBR / CMC: SP with a mass ratio of 40:40:10:5:5. The current collector of the negative electrode adopts carbon-coated copper foil.
[0084] The negative electrode components are pulped, coated, rolled and cut according to conventional methods to obtain a negative electrode.
[0085] (3) Assembly
[0086] The positive electrode, negative electrode and separator PP prepared above are wound and assembled according to a monomer structure.
[0087] The monomer is dried and injected, and the electrolyte uses DEC / EMC / PC solvent and Li + / Na + (1:1) positive ions and PF 6 - / FSI - The electrolyte is composed of (1:1) negative ions. The monomers are subjected to formation and electrical performance tests, as well as low temperature performance tests and 5C cycle life tests.
[0088] Example 5
[0089] A hybrid capacitor of a lithium-sodium dual-ion system comprises a positive electrode, a negative electrode and an electrolyte.
[0090] (1) The formula of the positive electrode slurry in the inner layer of the positive electrode is LiFeMnPO 4: The mass ratio of mesoporous carbon:PTFE:Ketchen carbon is 80:10:4:6. The formula of the outer positive electrode slurry is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 The mass ratio of mesoporous carbon:PTFE:Ketjen carbon is 60:30:5:5. The positive electrode current collector is corroded aluminum foil.
[0091] The inner positive electrode slurry and the outer positive electrode slurry are mixed in a corresponding ratio to form a slurry, and the viscosity is controlled at 2000-3000cps. The two slurries are coated on the corroded aluminum foil at the same time, and the coating surface density ratio of the inner and outer slurries is controlled to be 1:1. The positive electrode coating thickness is 130μm on a single side, and the positive electrode is obtained after rolling and slitting.
[0092] (2) Negative electrode
[0093] The formula of negative electrode components is hard carbon: mesoporous carbon: PAA: SP with a mass ratio of 80:10:5:5. The negative electrode current collector is copper foil.
[0094] The negative electrode components are pulped, coated, rolled and cut according to conventional methods to obtain a negative electrode.
[0095] (3) Assembly
[0096] The positive electrode, negative electrode and PET separator prepared above are wound and assembled according to a monomer structure.
[0097] The monomer is dried and injected, and the electrolyte uses EC / EMC solvent and Li + / Na + (1:1) positive ions and BF 4 - The electrolyte is composed of negative ions. The monomers are subjected to formation and electrical performance tests, as well as low temperature performance tests and 5C cycle life tests.
[0098] Example 6
[0099] A hybrid capacitor of a lithium-sodium dual-ion system comprises a positive electrode, a negative electrode and an electrolyte.
[0100] (1) The formula of the positive electrode slurry of the inner positive electrode is NCA: carbon aerogel: PVDF: graphene with a mass ratio of 80:10:4:6. The formula of the positive electrode slurry of the outer positive electrode is PBAs: carbon aerogel: PVDF: graphene with a mass ratio of 60:30:5:5. The positive electrode current collector is corroded aluminum foil.
[0101] The inner positive electrode slurry and the outer positive electrode slurry are mixed in a corresponding ratio to form a slurry, and the viscosity is controlled at 2000-3000cps. The two slurries are coated on the corroded aluminum foil at the same time, and the coating surface density ratio of the inner and outer slurries is controlled to be 1:1. The positive electrode coating thickness is 130μm on a single side, and the positive electrode is obtained after rolling and slitting.
[0102] (2) Negative electrode
[0103] The negative electrode component formula is soft carbon: carbon aerogel: PAA: SP with a mass ratio of 80:10:5:5. The negative electrode current collector is copper foil.
[0104] The negative electrode components are pulped, coated, rolled and cut according to conventional methods to obtain a negative electrode.
[0105] (3) Assembly
[0106] The positive electrode, negative electrode and separator polyimide prepared above are wound and assembled according to a monomer structure.
[0107] The monomer is dried and injected, and the electrolyte is EC / DMC solvent and Li + / Na + (1:1) positive ions and ClO 4 - The electrolyte is composed of negative ions. The monomers are subjected to formation and electrical performance tests, as well as low temperature performance tests and 5C cycle life tests.
[0108] Comparative Example
[0109] Comparative Example 1
[0110] The difference from Example 1 is that the positive electrode is only coated with the inner layer positive electrode slurry formula, and the electrolyte also contains only lithium ions as a positive ion.
[0111] A capacitor consisting of a positive electrode, a negative electrode, and an electrolyte.
[0112] (1) Positive electrode
[0113] The formula of the positive electrode slurry is lithium iron phosphate: activated carbon: SBR / CMC: SP with a mass ratio of 80:10:4:6. The positive electrode current collector is carbon-coated aluminum foil.
[0114] The positive electrode slurry is mixed in proportion to form a slurry, and the viscosity is controlled at 2000-3000cps. The slurry is coated on a carbon-coated aluminum foil, and the positive electrode coating thickness is 130μm on a single side. The positive electrode is obtained by rolling and cutting.
[0115] (2) Negative electrode
[0116] The formula of negative electrode components is hard carbon: soft carbon: activated carbon: SBR / CMC: SP with a mass ratio of 40:40:10:5:5. The current collector of the negative electrode adopts carbon-coated copper foil.
[0117] The negative electrode components are pulped, coated, rolled and cut according to conventional methods to obtain a negative electrode.
[0118] (3) Assembly
[0119] The positive electrode, negative electrode and separator PP prepared above are wound and assembled according to a monomer structure.
[0120] The monomer is dried and injected, and the electrolyte uses DEC / EMC / PC solvent, Li + Positive ions and PF 6 - / FSI - The electrolyte is composed of (1:1) negative ions. The monomers are subjected to formation and electrical performance tests, as well as low temperature performance tests and 5C cycle life tests.
[0121] Comparative Example 2
[0122] The difference from Example 1 is that graphite is used as the active material of the negative electrode.
[0123] A capacitor consisting of a positive electrode, a negative electrode, and an electrolyte.
[0124] (1) The formula of the positive electrode slurry of the inner positive electrode layer is lithium iron phosphate: activated carbon: SBR / CMC: SP with a mass ratio of 80:10:4:6. The formula of the positive electrode slurry of the outer positive electrode layer is sodium iron pyrophosphate: activated carbon: PVDF: SP with a mass ratio of 60:30:5:5. The positive electrode current collector is carbon-coated aluminum foil.
[0125] The inner positive electrode slurry and the outer positive electrode slurry are mixed in a corresponding ratio to form a slurry, and the viscosity is controlled at 2000-3000cps. The two slurries are coated on the carbon-coated aluminum foil at the same time, and the coating surface density ratio of the inner and outer slurries is controlled to be 3:4. The positive electrode coating thickness is 130μm on a single side, and the positive electrode is obtained after rolling and slitting.
[0126] (2) Negative electrode
[0127] The formula of negative electrode components is graphite: activated carbon: SBR / CMC: SP with a mass ratio of 80:10:5:5. The current collector of the negative electrode is carbon-coated copper foil.
[0128] The negative electrode components are pulped, coated, rolled and cut according to conventional methods to obtain a negative electrode.
[0129] (3) Assembly
[0130] The positive electrode, negative electrode and separator PP prepared above are wound and assembled according to a monomer structure.
[0131] The monomer is dried and injected, and the electrolyte uses DEC / EMC / PC solvent and Li + / Na + (1:1) positive ions and PF 6 - / FSI - The electrolyte is composed of (1:1) negative ions. The monomers are subjected to formation and electrical performance tests, as well as low temperature performance tests and 5C cycle life tests.
[0132] Comparative Example 3
[0133] The difference from Example 1 is that the ratio of the inner and outer coating surface density of the positive electrode and the positive ion Li + / Na + The ratio is 5:1, which is higher than the preferred range.
[0134] A hybrid capacitor of a lithium-sodium dual-ion system comprises a positive electrode, a negative electrode and an electrolyte.
[0135] (1) The formula of the positive electrode slurry of the inner positive electrode layer is lithium iron phosphate: activated carbon: SBR / CMC: SP with a mass ratio of 80:10:4:6. The formula of the positive electrode slurry of the outer positive electrode layer is sodium iron pyrophosphate: activated carbon: PVDF: SP with a mass ratio of 60:30:5:5. The positive electrode current collector is carbon-coated aluminum foil.
[0136] The inner positive electrode slurry and the outer positive electrode slurry are mixed in a corresponding ratio to form a slurry, and the viscosity is controlled at 2000-3000cps. The two slurries are coated on the carbon-coated aluminum foil at the same time, and the coating surface density ratio of the inner and outer slurries is controlled to be 5:1. The positive electrode coating thickness is 130μm on a single side (i.e., the thickness of the inner and outer layers on one side of the current collector) and the positive electrode is obtained after rolling and cutting.
[0137] (2) Negative electrode
[0138] The formula of negative electrode components is hard carbon: soft carbon: activated carbon: SBR / CMC: SP with a mass ratio of 40:40:10:5:5. The current collector of the negative electrode adopts carbon-coated copper foil.
[0139] The negative electrode components are pulped, coated, rolled and cut according to conventional methods to obtain a negative electrode.
[0140] (3) Assembly
[0141] The positive electrode, negative electrode and separator PP prepared above are wound and assembled according to a monomer structure.
[0142] The monomer is dried and injected, and the electrolyte uses DEC / EMC / PC solvent and Li + / Na + (5:1) positive ions and PF 6 - / FSI - The electrolyte is composed of (1:1) negative ions. The monomers are subjected to formation and electrical performance tests, as well as low temperature performance tests and 5C cycle life tests.
[0143] Comparative Example 4
[0144] The difference from Example 1 is that the ratio of the inner and outer coating surface density of the positive electrode and the positive ion Li + / Na + The ratio is 1:5, which is lower than the preferred range.
[0145] A hybrid capacitor of a lithium-sodium dual-ion system comprises a positive electrode, a negative electrode and an electrolyte.
[0146] (1) The formula of the positive electrode slurry of the inner positive electrode layer is lithium iron phosphate: activated carbon: SBR / CMC: SP with a mass ratio of 80:10:4:6. The formula of the positive electrode slurry of the outer positive electrode layer is sodium iron pyrophosphate: activated carbon: PVDF: SP with a mass ratio of 60:30:5:5. The positive electrode current collector is carbon-coated aluminum foil.
[0147] The inner positive electrode slurry and the outer positive electrode slurry are mixed in a corresponding ratio to form a slurry, and the viscosity is controlled at 2000-3000cps. The two slurries are coated on the carbon-coated aluminum foil at the same time, and the coating surface density ratio of the inner and outer slurries is controlled to be 1:5. The positive electrode coating thickness is 130μm on a single side (i.e., the thickness of the inner and outer layers on one side of the current collector) and the positive electrode is obtained after rolling and cutting.
[0148] (2) Negative electrode
[0149] The formula of negative electrode components is hard carbon: soft carbon: activated carbon: SBR / CMC: SP with a mass ratio of 40:40:10:5:5. The current collector of the negative electrode adopts carbon-coated copper foil.
[0150] The negative electrode components are pulped, coated, rolled and cut according to conventional methods to obtain a negative electrode.
[0151] (3) Assembly
[0152] The positive electrode, negative electrode and separator PP prepared above are wound and assembled according to a monomer structure.
[0153] The monomer is dried and injected, and the electrolyte uses DEC / EMC / PC solvent and Li + / Na + (1:5) positive ions and PF6 - / FSI - The electrolyte is composed of (1:1) negative ions. The monomers are subjected to formation and electrical performance tests, as well as low temperature performance tests and 5C cycle life tests.
[0154] Performance Testing
[0155] The performance of each embodiment and comparative example was tested, and the test method was based on GBT34870.1 "Supercapacitor General Principles Part 1". Among them, the voltage range of Example 4 is 4.2-2.5V, and the other voltage ranges are 3.6-2.0V. The cycle voltage range is the same as the capacity test voltage range. The discharge cut-off voltage of the low temperature performance test is 1.5V (Example 4 is 2.0V). The results are shown in the following table.
[0156]
[0157] It can be seen from the above table that the double-layer electrode structure hybrid capacitor of the lithium-sodium dual ion system prepared in each embodiment of the present invention further improves the low-temperature charge and discharge performance of the hybrid capacitor while maintaining the energy density unchanged, and improves the rate performance of the hybrid capacitor.
[0158] Comparing Examples 1, 2, and 3, it can be seen that the energy density increases with the increase in the proportion of lithium hybrid capacitors, while the low-temperature rate and lifespan decrease. Further, from Comparative Examples 2 and 3 and Comparative Examples 3 and 4, it can be seen that the surface density of the double-layer electrode is 1:4 to 4:1, and the comprehensive performance is better. The surface density of lithium hybrid capacitors continues to increase, and the energy density increases, but the low-temperature rate and lifespan decrease significantly. The surface density of sodium hybrid capacitors continues to increase, and the energy density decreases, but the lifespan and low-temperature rate performance are not significantly improved.
[0159] Compared with Example 1: ① The positive electrode of the capacitor in Example 1 contains only lithium ions and no sodium ions. The low-temperature high rate and lifespan are significantly reduced, indicating that the sodium ion layer can improve the low-temperature resistance of the capacitor. ② The negative active material of the hybrid capacitor in Example 2 uses graphite. The rate discharge capability, low-temperature performance and lifespan are not as good as those in Example 1, indicating that the negative active material of the present invention uses soft carbon and hard carbon to achieve good results. In addition, due to the high capacity of hard carbon, it is mainly used in conjunction with sodium capacitors.
[0160] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A multilayer composite positive electrode of a lithium-sodium dual ion system, characterized in that: The current collector is in the middle, the inner layer is coated on both sides of the current collector, and the outer layer is coated on the outside of the inner layer. The inner layer uses a lithium ion / capacitor carbon hybrid electrode, and the outer layer uses a sodium ion / capacitor carbon hybrid electrode. The coating surface density ratio of the inner layer and the outer layer is 1:(0.25-4).
2. The multilayer composite positive electrode of the lithium-sodium dual ion system according to claim 1, characterized in that: The inner layer comprises 50-80% by mass of lithium metal oxide, and the lithium metal oxide is selected from one or more of LiFePO4, NCM / NCA ternary positive electrode, and LiFeMnPO4.
3. The multilayer composite positive electrode of the lithium-sodium dual ion system according to claim 2, characterized in that: The inner layer contains 50-80% by mass of lithium metal oxide, 10-40% by mass of capacitor carbon, 4-10% by mass of binder and 4-10% by mass of conductive agent, and the sum of the mass fractions of the components is 100%.
4. The multilayer composite positive electrode of the lithium-sodium dual ion system according to claim 1, characterized in that: The outer layer comprises 40-70% by mass of sodium metal compound, and the sodium metal compound is selected from one or more of polyanion type, oxide type and Prussian blue type sodium metal compound materials.
5. The multilayer composite positive electrode of the lithium-sodium dual ion system according to claim 4, characterized in that: The outer layer contains 40-70% by mass of sodium metal compound, 20-50% by mass of capacitor carbon, 4-10% by mass of binder and 4-10% by mass of conductive agent, and the sum of the mass fractions of the components is 100%.
6. The multilayer composite positive electrode of the lithium-sodium dual ion system according to claim 3 or 5, characterized in that: The capacitor carbon is selected from one or more of activated carbon, mesoporous carbon, and carbon aerogel; the binder is selected from one or more of SBR, CMC, PTFE, PVDF, and PAA; and the conductive agent is selected from one or more of conductive carbon black, Ketjen carbon, graphene, and carbon nanotubes.
7. A hybrid capacitor of a lithium-sodium dual ion system, characterized in that: The positive electrode of the hybrid capacitor is a multilayer composite positive electrode of the lithium-sodium dual ion system as described in any one of claims 1-6.
8. The hybrid capacitor of the lithium-sodium dual ion system according to claim 7, characterized in that: The negative electrode contains 60-85% active material, 5-30% capacitor carbon, 4-10% binder, and 4-10% conductive agent by mass, and the sum of the proportions of each component is 100%; the active material is a mixture of soft carbon and hard carbon.
9. The hybrid capacitor of the lithium-sodium dual ion system according to claim 7 or 8, characterized in that: The electrolyte includes positive ions, negative ions and ester solvents. The positive ions are composed of Li + and Na + Composition: Anion is selected from BF4 - 、ClO4 - PF6 - 、FSI - One or more of; the ester solvent is selected from one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, and propylene carbonate.
10. The method for preparing a hybrid capacitor of a lithium-sodium dual ion system according to any one of claims 7 to 9, characterized in that: The following steps are involved: 1) Mix the inner positive electrode slurry and the outer positive electrode slurry to form a slurry with a viscosity controlled at 2000-3000 cps; 2) Coating the two slurries on the positive electrode current collector at the same time, controlling the coating surface density ratio of the two slurries, and rolling and cutting to obtain the positive electrode; 3) Slurrying, coating, rolling and cutting the negative electrode components to obtain the negative electrode; 4) Wind the positive electrode, negative electrode and separator and assemble them according to the monomer structure; then dry, inject liquid, age and test.
Citation Information
Patent Citations
Li-Ion Hybrid Capacitors
CN105161309B
Composite positive plate of lithium battery, composite negative plate of lithium battery, preparation method of composite positive plate and composite negative plate and lithium battery
CN105226234A
Composite positive pole piece, preparation method thereof, and lithium ion battery containing the pole piece
CN109585780A